Neurometabolic and microstructural alterations following a sports-related concussion in female athletes. (August 2013) - Chamard, Emilie; Lassonde, Maryse; Henry, Luke; Tremblay, Julie; Boulanger, Yvan; De Beaumont, Louis; Théoret, Hugo
Abstract Background: Sports-related concussions are a major public health concern affecting millions of individuals annually. Neurometabolic and microstructural alterations have been reported in the chronic phase following a concussion in male athletes, while no study has investigated these alterations in female athletes. Methods: Neurometabolic and microstructural alterations following a concussion were investigated by comparing 10 female athletes with a concussion and 10 control female athletes, using magnetic resonance spectroscopy (MRS) and diffusion tensor imaging (DTI). Athletes with concussion were scanned at least 7 months post-concussion (mean = 18.9 months). Results: MRS revealed a significant lower level of myo-inositol in the hippocampus and the primary motor cortices (M1) bilaterally. DTI analysis using Tract-Based Spatial Statistics (TBSS) showed no difference in fractional anisotropy (FA) while higher level of mean diffusivity (MD) in athletes with concussion was detected in large white matter tracts including the forceps minors, inferior/superior longitudinal fasciculi, inferior fronto-occipital fasciculus, cingulum, uncinate fasciculus, anterior thalamic radiations and corticospinal tract. Moreover, a region of interest approach for the corpus callosum revealed a significant lower level of FA in the segment containing fibres projecting to M1. Conclusions: This study demonstrates persistent neurometabolic and microstructural alterations in female athletes suffering a sports-related concussion.